Efficacy of ferric carboxymaltose versus iron sucrose in non-dialysis dependent chronic kidney disease - Kamlesh Kumar; Sarfaraz Sarwar; Rabeea Abbas; Nida Vallani; Nazarul Hassan Jaffry; Zara Khan (Journal of the Pakistan Medical Association, 2026)
Objective: To determine the efficacy of ferric carboxymaltose versus iron sucrose in non-dialysis-dependent chronic kidney disease patients. Method: The randomised controlled trial was conducted at the Nephrology Outpatient Department of the Sindh Institute of Urology and Transplantation, Karachi, from April to September 2025, and comprised patients with non-dialysis-dependent chronic kidney disease stages 3-5a and iron deficiency anaemia. The patients were randomised into ferric carboxymaltose group A and iron sucrose group B. Baseline assessments were compared with those taken at four and eight weeks. Data was analysed using SPSS 22. Results: Of the 128 patients, 64(50%) were in group A; 37(57.8%) males and 27(42.2%) females with mean age 55.1±12.6 years. The remaining 64(50%) patients were in group B; 35(54.7%) males and 29(45.3%) females with mean age 54.2±13.1 years (p>0.05). Baseline haemoglobin did not differ between the groups (p=0.81). Transferrin saturation and serum ferritin improved significantly more in group A compared to group B (p<0·001). Patients in both the groups tolerated the treatment well, with no significant difference in adverse events (p=0.24). Conclusion: Ferric carboxymaltose showed greater effectiveness compared to iron sucrose in the treatment of anaemia and iron stores in non-dialysis-dependent chronic kidney disease patients with comparable safety. Key Words: Chronic kidney disease, Ferric carboxymaltose, Iron deficiency anaemia, Iron sucrose, Intravenous iron therapy.